FAKTOR INTERNAL PENYERAPAN TENAGA KERJA DI PULAU JAWA - Haydarsyah, M. Zidan; Nilasari, Aprillia (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
This study aims to determine the impact of independent variables, namely Population, Education Level, and Minimum Wage on the dependent variable, namely Labor Absorption, partially or simultaneously in Java Island in 2017-2023. This study uses a quantitative approach and uses secondary data obtained from the Central Statistics Agency. The population in this study is all data on population, education level, provincial minimum wage, and number of workers in provinces in Java Island, while the sample is all data on population, education level, provincial minimum wage, and number of workers in provinces in Java Island in a period of 7 years, namely 2017 - 2023. The analysis method used is panel data regression. In this study, the results obtained are that the Population and Education Level variables have a positive impact on Labor Absorption, while the Minimum Wage variable does not affect Labor Absorption, and all independent variables have a simultaneous or joint effect on Labor Absorption in Java Island. This simultaneous influence has a significance level of 99.73% while the other 0.27% is explained by other variables outside the variables in the study.